Effect of Internal Limiting Membrane peeling on Success of Pars Plana Vitrectomy in Epi-Macular Membrane: Doi: 10.36351/pjo.v41i2.1922 - Fazaa, Ali Abbas Hassan; Hasan AbdulAmirAl-Maamar; Abdulla, Mudhher Ghani (Pakistan Journal of Ophthalmology, 2025)
Purpose: To determine the effect of internal limiting membrane (ILM) peeling on the success of pars plana vitrectomy (PPV). Study Design: Quasi experimental study. Place and Duration of Study: Al-Firdous Private Eye Hospital from 2021 and 2022. Method: This study included patients with an epiretinal macular membrane (EMM) and visual symptoms who were scheduled for PPV. Patients with diabetes mellitus, cellophane maculopathy, or those without symptoms were excluded. A total of 40 patients were enrolled and divided into two groups (20 in each) using convenient sampling. Group A underwent PPV with EMM and ILM peeling. Group B underwent PPV with EMM but without ILM peeling. The primary outcome was the recurrence of EMM within two years. Qualitative data were analyzed using the Chi-square test in Microsoft Excel, with a significance level set at p < 0.05. Results: The mean age in Group A was 43 ± 3.2 years, while in Group B, it was 45 ± 3.7 years (p > 0.5). Males comprised most participants (67.7%, n=27), with 16 males in Group B. Recurrence of EMM requiring a second PPV was observed in 6 patients (30%) from Group B, whereas no recurrence occurred in Group A (p = 0.007). Conclusion: ILM peeling significantly reduces the recurrence rate of EMM following PPV, demonstrating its superiority in surgical success.